Між фольклором і політикою - Ріхтман-Аугуштін, Д. (Народна творчість та етнологія, 2011)
Folklore is not playing and dancing show festivals and other mass measures. His function is not restrictend to preparation of collections of verbal folk work. It is important to realize that folklore is not living isolated from policy, and that he is often attracted to her. Secret services in industry of folklore were often an important constituent of certain political fight for a national revival and national identity. It is indisputably that nearby Croatian and Serbian national cultures, as well as there folk culture and folklore, have not only general lines but also origins of similar genres, themes and reasons taking into account their linguistic affinity. The tendencies of giving of certain standards or folklore genres as general signs of South Slavonic unity and simila fate of both nations had also a certain political motivation.